Dufour and Soret Effects on Steadv MHD Combined Free-Forced Convective and Mass Transfer Flow Past a Semi-Infinite Vertical Plate - Alam, Shariful; Rahman, M. M.; Maleque, Abdul; Ferdows, M. (Science & Technology Asia, 2015)
-